The effect of medroxyprogesterone acetate on pregnancy rates in reindeer calves (Rangifer tarandus) - Ropstad, Erik; Helland, Gaute; Hansen, Helge; Lenvik, Dag; Solberg, Eva Tangen (Rangifer, 1993)
In September 1990, a total of 69 calves with a minimum body weight of 46 kg were allocated into two groups, one treated with a single injection of 75 mg medroxyprogesterone acetate (N = 35), the other serving as control (N=34). Blood samples were collected for progesterone analysis in December 1990 and 1991. Udder palpation was performed in July and September 1990. Treated animals had significantly lower plasma progesterone levels in December 1990. The pregnancy rate as determined by udder palpation was 16.7% for treated animals and 48.3% for controls (P<0.01). All animals which were found to be pregnant had high progesterone levels (>5 ng/ml) the following winter. The mean body weight increase was 5.1 kg lower in females which kept their calves until September than in barren females (P<0.05). More than 50% of the pregnant females lost their calves during the summer.